Allogeneic Cultivated Limbal Epithelial Sheet Transplantation in Reconstruction of Conjunctival Sac After Chemical and Thermal Burns - Wang, Ting; Shan, Fengmei; Zhou, Qingjun; Shi, Weiyun; Xie, Lixin (Frontiers in Medicine, 2021)
The study aims to evaluate the effect of allogeneic cultivated limbal epithelial cell sheet transplantation (CLET) in reconstructing conjunctival sac for severe symblepharon after chemical and thermal burns. A retrospective, noncomparative case series. Thirty-six eyes (36 patients) underwent CLET for severe symblepharon and conjunctival sac stenosis or atresia. Inclusion criteria were: at least with 2 quarters of symblepharon, and conjunctival sac contraction; the pseudopterygium encroaching onto the cornea; limitation of eye and eyelid movement; 6 months after injury. Symblepharon was separated, and pseudopterygium was preserved to replace the palpebral conjunctiva. Allogeneic cultivated limbal epithelial cell sheet using human amniotic membrane as a carrier was transplanted into the recipient's eye to reconstruct the conjunctival sac. The effect of conjunctival sac reconstruction, eye and eyelid movement, ocular surface restitution, and symblepharon recurrence were analyzed after surgery. Symblepharon was completely relieved in 30 of the 36 eyes (83.3%) by a single surgical procedure, with fornix reconstruction, as well as free movement of eye globe and eyelids. Strip-like symblepharon remained in 6 eyes (16.7%) and was completely relieved after the second CLET. 20 patients without visual function received prostheses 3 months after surgery. During the follow-up period, no one had symblepharon recurrence. The transplantation of cultivated allogeneic limbal epithelial sheets offers an effective and safe alternative in the treatment of symblepharon and reconstruction of conjunctival sac in eyes with severe ocular burns, with donor cells obtained abundantly.